2021 Common Work of Art - Marianna Kistler Beach Museum of Art (K-State First, 2021)
This resource developed by the K-State Marianna Kistler Beach Museum of Art, announces the selection of the 2021 Common Work: Neal Ambrose-Smith's From Upstream I Caught Fish, 2008. The Beach Museum staff provide context on the significance of this selected work and its relationship with the 2021 First Book: Cherie Dimaline's The Marrow Thieves.
Keywords: Common reading program; Marrow Thieves, The; First-year experience program; From Upstream I Caught Fish; Neal Ambrose-Smith; Marianna Kistler Beach Museum of Art